2002
DOI: 10.1007/s00221-002-1231-5
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic pharmacology in the turtle accessory optic system

Abstract: The accessory optic system of the turtle (the basal optic nucleus, BON) receives both excitatory and inhibitory inputs that are direction-sensitive. When the dorsal midbrain is ablated, only the monosynaptic direction-sensitive input from the retina to the BON remains. To better understand the central visual processing performed by the accessory optic system, this study identifies the neurotransmitters and their receptors that mediate the synaptic excitation and inhibition of BON cells. We used a reduced in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…The importance of such an arrangement is that it allows 1) enhanced spatial coding (enhanced receptive fields) by convergence many retinal ganglion cells directly on the AOS neuron and indirectly through retino-NLM-nBON projections, 2) gain enhancement on the AOS neurons, and/or 3) sensory processing or tuning through a convergence of excitatory and inhibitory inputs (Ariel and Kogo, 2001). Further pharmacological studies on the turtle AOS revealed that of the converging, direction-selective, inhibitory/excitatory inputs to the nBOR, the inhibitory inputs are blocked by bicuculline mediated by the retinal-pretectal connections acting upon GABA (A) receptors located on the nBOR neurons, whereas the excitatory input is from retinal glutaminergic retinal afferents, given that retinal excitation of the nBOR was blocked by an antagonist of the AMPA (alphaamino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) glutamate receptor subtype (Kogo and Ariel, 2002). The likely source of direction-selectivity of NOT/DTN neurons remains their retinal input from excitatory, on-center, direction-selective retinal ganglion cells (Oyster et al, 1972;Hoffmann and Stone, 1985.…”
Section: Gaba (Fig 9)mentioning
confidence: 99%
“…The importance of such an arrangement is that it allows 1) enhanced spatial coding (enhanced receptive fields) by convergence many retinal ganglion cells directly on the AOS neuron and indirectly through retino-NLM-nBON projections, 2) gain enhancement on the AOS neurons, and/or 3) sensory processing or tuning through a convergence of excitatory and inhibitory inputs (Ariel and Kogo, 2001). Further pharmacological studies on the turtle AOS revealed that of the converging, direction-selective, inhibitory/excitatory inputs to the nBOR, the inhibitory inputs are blocked by bicuculline mediated by the retinal-pretectal connections acting upon GABA (A) receptors located on the nBOR neurons, whereas the excitatory input is from retinal glutaminergic retinal afferents, given that retinal excitation of the nBOR was blocked by an antagonist of the AMPA (alphaamino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) glutamate receptor subtype (Kogo and Ariel, 2002). The likely source of direction-selectivity of NOT/DTN neurons remains their retinal input from excitatory, on-center, direction-selective retinal ganglion cells (Oyster et al, 1972;Hoffmann and Stone, 1985.…”
Section: Gaba (Fig 9)mentioning
confidence: 99%
“…Ariel and Kogo (2001), using a turtle brain stem preparation with the eyes attached, observed that visual stimuli provoked both excitation and inhibition of the nBOR neurones. These neurones also probably receive a tonic activation and inhibition from the retina and other cells (Kogo et al, 2002). The retinal slip signal may be due to these competing excitatory and inhibitory visual inputs.…”
Section: Structures and Mechanisms Underlying Context-dependantmentioning
confidence: 99%
“…The accessory optic system receives direct excitatory input from the retina (Kogo and Ariel 1997;Zhang and Eldred 1994) and indirect inhibitory input from the pretectum (Kogo et al 2002). Both excitatory and inhibitory responses to pattern motion on the contralateral retina are direction-sensitive (Ariel and Kogo 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The excitatory response from the retina is mediated entirely by AMPA receptors, while pretectal stimulation evokes an inhibitory response that is Cl Ϫ mediated and blocked by a GABA A receptor antagonist (Kogo et al 2002). The time course of nonlinear interactions of coincident excitation and inhibition were evaluated during whole cell patch recordings in the intact turtle brain stem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation